Implementation and outcomes of attachment of earnings orders, 1989-1991 - Ford, J. R. (UK Data Service, 1992)
The aim of this project was to provide information about the form and process of the implementation of 'attachment of earnings' orders, and to develop knowledge and understanding of the impact of this default recovery process on employers and employees.